Leonardo da Vinci's discovery of the dynamic soaring by birds in wind shear. (3rd October 2018) - Richardson, Philip L.
Abstract : Although Leonardo da Vinci (1452–1519) is well known to have studied bird flight, few people realize that he was the first to document flight manoeuvres now called dynamic soaring. Birds use these manoeuvres to extract energy from the gradient of wind velocity (wind shear) for sustained flight. In his Manuscript E ( ca 1513–1515) Leonardo described land birds performing flight manoeuvres that match those of albatrosses and other seabirds when they are engaged in dynamic soaring over the ocean. His description pre-dates by almost 400 years the first generally accepted explanation of the physics of this soaring technique by Lord Rayleigh in 1883. Leonardo's early description of dynamic soaring is one of his major aerodynamic discoveries.